Letter From the Editor. Issue 1 (2nd January 2019) - Rosenbloom, Sandra
Abstract : This issue is a meaningful one for me because a special section honors David Godschalk, a great scholar, researcher, practicing planner, and teacher who served as Editor of JAPA from 1968 through 1971. Godschalk died in January 2018; many of his former students and colleagues, all accomplished academics and practitioners themselves, immediately asked if they could do a special section of the journal honoring him. JAPA is clearly the right place to do so because he remained an active member of the Editorial Board until just months before his death, because he cared deeply about the journal, and because so much of his work is foundational for both planning practitioners and academics. He was, moreover, the Editor with the intelligence and good sense to publish an atypical article in 1969: Sherry Arnstein's "Ladder of Citizen Participation."